The Perpetuation of Stereotypes in Croatian Public Discourse : "Autistic" as a Pejorative = Perpeturianje stereotipa u hrvatskome javnom diskursu : uporaba riječi autističan u pejorativnome značenju - Patekar, Jakob (Array, 2021)
The way people are spoken or written about has a critical role in how they are perceived, and this in turn influences how they are positioned within a society – belonging to its core, the majority, or being relegated to the margins, the minority. Various authors have reflected on the role of language in dehumanizing, oppressing, and discriminating certain groups, be it the Jewish citizens during the Nazi regime in Germany, the Tutsi in the Rwandan genocide of 1994, black people in the United States since 1619, women throughout history, or gay and disabled people today, to name a few marginalized groups. In these and other cases, language was the first step in the othering and, consequently, the marginalization of a certain group. The aim of this paper is to explore the language of marginalization in Croatian public discourse, looking at how media workers and public figures contribute to stereotyping people with autism by using the words "autistic" and "autistically" as pejoratives. For this purpose, I analyzed one of the most visited newspaper websites in Croatia in relation to how these words are used. I found that journalists, writers, and politicians use "autistic" and "autistically" as pejoratives when they want to say that an individual, an institution, or a state is "out of touch with reality", "self-centered", "unresponsive". In addition, "autistic" and "autistically" are often used with the intent to insult, thus further imbuing these words with negative connotations. I conclude that raising awareness is needed among media workers and public figures so that they recognize the danger of stereotyping people with autism through the pejorative use of the words "autistic" and "autistically".